Echocardiographic signs of subclinical cardiac function impairment in Duchenne dystrophy gene carriers - Kincl, Vladimír; Panovský, Roman; Pešl, Martin; Máchal, Jan; Juříková, Lenka; Haberlová, Jana; Masárová, Lucia (Scientific reports, 2020)
To assess subclinical cardiac function impairment in Duchenne dystrophy (DMD) female carriers. Forty-four female subjects proved as DMD carriers underwent echocardiographic examination including tissue Doppler imaging (TDI) of mitral and tricuspid annulus. Seventeen age-matched healthy female subjects served as controls. A significant differences in peak systolic annular velocity (Sa) between carriers and controls were found for lateral and septal part of the mitral annulus and for tricuspid annulus (0.09 vs. 0.11 m/s, p < 0.001, 0.08 vs. 0.09 m/s, p < 0.01 and 0.13 vs. 0.14 m/s, p = 0.02 respectively). There was also difference in early diastolic velocity (Ea) of the septal part of the mitral annulus (0.11 vs. 0.13 m/s, p = 0.03). The subclinical deterioration of systolic function is presented even in asymptomatic DMD female carriers.
Keywords: dospělí; Muscular Dystrophy, Duchenne; heterozygot; Female; systola; dysfunkce levé srdeční komory; Adult; ženské pohlaví; Tricuspid Valve; Ventricular Dysfunction, Left; lidé; Heterozygote; dopplerovská echokardiografie; studie případů a kontrol; rychlost toku krve; Echocardiography, Doppler; Blood Flow Velocity; trikuspidální chlopeň; Case-Control Studies; Duchennova muskulární dystrofie; Systole; Mitral Valve; mitrální chlopeň; lidé středního věku; Middle Aged; Humans